2004
DOI: 10.1111/j.1538-7836.2004.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the 5′‐UTR of the tissue factor gene are associated with altered expression in human endothelial cells

Abstract: Summary.  Background: Enhanced tissue factor (TF) expression mediates many disease processes. Recently, four completely concordant polymorphisms were detected in the 5′‐UTR of the TF gene. Three were single base changes and one was an 18‐bp insertion/deletion at −1208. Objectives: This study was undertaken to determine if the I‐allele or the D‐allele would associate with elevated TF expression in human umbilical vein endothelial cells (HUVEC). Methods: HUVEC were genotyped by polymerase chain reaction for 18‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…This hypothesis is supported by in vitro studies by Terry et al showing an association of the TF promoter A haplotype (-1208Del) with higher TF mRNA levels and higher surface TF procoagulant activity in endothelial cells [17]. Moreover, although evaluation in silico in another study did not indicate effects of the 4 investigated polymorphisms on transcription factor binding [11], gel shift experiments by Terry et al indeed demonstrated such effects of the Del-1208Ins polymorphism, providing a possible explanation for the genotypic differences in TF expression and activity [17].…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This hypothesis is supported by in vitro studies by Terry et al showing an association of the TF promoter A haplotype (-1208Del) with higher TF mRNA levels and higher surface TF procoagulant activity in endothelial cells [17]. Moreover, although evaluation in silico in another study did not indicate effects of the 4 investigated polymorphisms on transcription factor binding [11], gel shift experiments by Terry et al indeed demonstrated such effects of the Del-1208Ins polymorphism, providing a possible explanation for the genotypic differences in TF expression and activity [17].…”
Section: Discussionmentioning
confidence: 64%
“…This hypothesis is supported by in vitro studies by Terry et al showing an association of the TF promoter A haplotype (-1208Del) with higher TF mRNA levels and higher surface TF procoagulant activity in endothelial cells [17]. Moreover, although evaluation in silico in another study did not indicate effects of the 4 investigated polymorphisms on transcription factor binding [11], gel shift experiments by Terry et al indeed demonstrated such effects of the Del-1208Ins polymorphism, providing a possible explanation for the genotypic differences in TF expression and activity [17]. An influence on local TF activity in the vessel wall may in turn modulate processes involved in atherosclerosis such as inflammation and VSMC migration and proliferation [2,9,10,[25][26][27][28][29][30], which could result in measurable differences in C-IMT as observed in this study.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations